Developing consumption feedback principles for monthly utility bills informed by behavioural economics: evidence from controlled experiments - Brühl, Johanna Maria (School of Economics, 2017)
Better feedback principles for the utility bills in South Africa need to be developed. Utility providers might be able to "nudge" consumers towards more desirable consumption patterns by delivering simpler and better feedback informed by applied behavioural sciences. Two sets of controlled experiments were conducted with over 1,500 subjects to identify bill design strategies that could overcome two major barriers to effective consumption feedback: • the complexity of the utility bill, especially with regards to tariff calculations, and • consumer's declining mindfulness of utility consumption between billing moments. The "Utility Bill Redesign" experiment, using a randomised control trial, investigates how improving billing feedback design increases consumer's understanding of energy usage and costs. More than 1,300 participants are randomly assigned to different treatment groups and receive one of nine redesigned utility bills or the current standard bill. Thereafter, participant's understanding of the bill they received is tested through a questionnaire. We find that restructuring the bill in a logical order and displaying the amount of electricity consumed in each tariff block with separate bar graphs is a successful way to increase consumer understanding of the bill, especially with regards to the step tariff. Further, the results clearly show that consumers are unable to make sense of a utility bill that is not in their home language, even when adding utility specific symbols. We conclude that significant low-cost improvements can be made to utility bills to increase consumer comprehension. In the "Attention Redirection" experiment, participants are assigned to different treatment groups and are given an online task that requires daily attention and effort in order to maximise pay-offs. We find that daily SMS reminders significantly redirect attention to the daily task. A blank graph, given to participants at the beginning of the experiment to assist them in self-managing their behaviour, has no effect on task adherence. The results illustrate how inattention routinely leads to sub-optimal behaviour in a specific task area and the resulting welfare loss. A purely bill-based strategy is rendered unsuccessful.